GEOPHYSICAL STUDIES AND TECTONISM OF THE HELLENIDES - Makris, J. (Bulletin of the Geological Society of Greece, 2010)
By constraining gravity modelling by Deep Seismic Soundings (DSS) and the Bouguer gravity field of Greece a 3-D density-velocity model of the crust and upper mantle was developed. It was shown that in the north Aegean Trough and the Thermaikos Basins the sediments exceed 7 km in thickness. The basins along the western Hellenides and the coastal regions of western Greece are filled with sediments of up to 10 km thickness, including the Prepulia and Alpine metamorphic limestones. The thickest sedimentary series however, were mapped offshore southwest and southeast of Crete and are of the order of 12 to 14 km. The crust along western Greece and the Peloponnese ranges between 42 and 32 km thickness while the Aegean region is floored by a stretched continental crust varying between 24 to 26 km in the north and eastern parts and thins to only 16 km at the central Cretan Sea. The upper mantle below the Aegean Sea is occupied by a lithothermal system of low density (3.25 gr/cm³) and Vp velocity (7.7 km/s), which is associated with the subducted Ionian lithosphere below the Aegean Sea. Isostasy is generally maintained at crustal and subcrustal levels except for the compressional domain of western Greece and the transition between the Mediterranean Ridge and the continental backstop. The isotherms computed from the Heat Flow density data and the density model showed a significant uplift of the temperature field below the Aegean domain. The 400°C isotherm is encountered at less than 10 Km depth. Tectonic deformation is controlled by dextral wrench faulting in the Aegean domain, while western Greece is dominated by compression and crustal shortening. Strike-slip and normal faults accommodate the western Hellenic thrusts and the westwards sliding of the Alpine napes, using the Triassic evaporates as lubricants.